Effect of silver nanoparticles on Sm3+ luminescence enhancement in tellurite glass. (2018) - Ruangtaweep, Y.; Yasaka, P.; Kaewkhao, J.
Abstract: The enhancement of luminescence properties of Sm 3+ in tellurite glasses containing silver nanoparticles (AgNPs) have been investigated. The glass samples with chemical composition of (53.5-x(TeO2 : 10ZnO: 35BaO: 1.5Sm2 O3 : xAgNPs (where x= 0.00, 0.01, 0.02, 0.03, 0.04, and 0.05% by mol) were prepare by the conventional melt quenching technique. The results show that the excitation and emission intensity of glass samples are increased with increasing of AgNPs concentrations. The excitation spectra were obtained by monitoring in the wavelength region 250–550 nm at emission wavelength 600 nm. The excitation bands are identified at 346, 363, 377, 405, 439, 474 and 527 nm corresponding to the transitions from the ground state 6 H5/2 to 4 D7/2, 4 D3/2, 6 P7/2, 6 P3/2, 6 P3/2, 4 G9/2, 4 I11/2 and 4 F3/2 excited states, respectively. The emission spectra were recorded in the wavelength region 500–750 nm using 405 nm excited wavelength. The emission peaks are observed at 563 (green), 600 (orange), 645 (red) and 707 (red) nm which are attributed to 4 G5/2 → 6 H5/2, 4 G5/2 → 6 H7/2, 4 G5/2 → 6 H9/2 and 4 G5/2 → 6 H11/2 transitions, respectively. The results confirm the luminescence enhancement of Sm 3+ ion in glass matrix.